POLA KOMUNIKASI KELOMPOK FANSITE EXONESIA DALAM MEMBANGUN EKSISTENSI DALAM LINGKUP PENGGEMAR K-POP - Debbiani Nurinda (Universitas Mercu Buana, 2019)
The development of technology encourages globalization which gives birth to many special phenomena and one of them is popular culture. Popular culture deals with everyday problems such as superstars, fashion, transportation, lifestyle, etc. that can be enjoyed by all people or certain people. K-Pop is one of the popular cultural phenomena that is being talked about by the people of Indonesia. Present with the concept of boyband and girlband, K-POP is loved by many young people and becomes a separate phenomenon in the midst of social life. This K-POP fever is characterized by the presence of fans or fansite, where the community only discusses one boy band or K-POP artist they admire.The focus of this research is to see how the EXOnesia Fansite Group Communication Pattern in Building Existence in the K-POP Enthusiasts Scope. This study uses qualitative research methods with participant observation research methods. Data collection used is in-depth interviews and observations. Based on research and observations conducted by researchers, EXOnesia's fansite community communication pattern is to use a two-way communication pattern where the communication process carried out by this community results in reciprocity or response when the message / information is sent by the giver to the recipient. where in the fanite members of the community do not have boundaries between superiors and subordinates, so that the patterns of interaction that occur within it just flow informally.